2010
DOI: 10.1111/j.1365-2435.2009.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet crown colouration affects contest outcomes among male blue tits, but only in the absence of prior encounters

Abstract: Summary1. Static animal colour patches may function among competitors to minimize conflict escalation over resources, by serving as a signal of resource holding potential or aggressiveness. Empirical evidence for the use of colour patches in conflict resolution is largely restricted to pigment-based colours (melanins and carotenoids) and rarely defines the context in which the signals are used. 2. Here we test whether structural-based ultraviolet (UV) crown colouration functions in conflict resolution among dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 67 publications
3
41
0
Order By: Relevance
“…In line with predictions of the badge of status hypothesis (Rohwer 1975;Maynard Smith and Harper 2003), UV reflectance influences either aggressive behaviors of male rivals or the outcome of contest in blue tits, sticklebacks, damselfishes, and several species of lizards (Alonso-Alvarez et al 2004;Siebeck 2004;Stapley and Whiting 2006;Whiting et al 2006;Rick and Bakker 2008;Rémy et al 2010: Vedder et al 2010Bajer et al 2011; and see a review by Olsson et al 2013). Yet, in wall lizards, we found no difference in contest scores and agonistic behaviors between male rivals in relation to UV treatments.…”
Section: Uv Visual Signals In Aggressive Interactionsmentioning
confidence: 62%
See 2 more Smart Citations
“…In line with predictions of the badge of status hypothesis (Rohwer 1975;Maynard Smith and Harper 2003), UV reflectance influences either aggressive behaviors of male rivals or the outcome of contest in blue tits, sticklebacks, damselfishes, and several species of lizards (Alonso-Alvarez et al 2004;Siebeck 2004;Stapley and Whiting 2006;Whiting et al 2006;Rick and Bakker 2008;Rémy et al 2010: Vedder et al 2010Bajer et al 2011; and see a review by Olsson et al 2013). Yet, in wall lizards, we found no difference in contest scores and agonistic behaviors between male rivals in relation to UV treatments.…”
Section: Uv Visual Signals In Aggressive Interactionsmentioning
confidence: 62%
“…However, the absence of significant effects of a reduced UV coloration on agonistic behaviors and contest outcomes is not entirely surprising because the badge of status hypothesis predicts that color patches are more influential during the first stages of conflict resolution, when individuals are not familiarized to each other. For example, Rémy et al (2010) and Vedder et al (2010) demonstrated effects of UV coloration on male-male interactions between unfamiliar individuals only. In our study, the behavioral profiles of males changed significantly after the first trial, suggesting that rivals quickly became familiar.…”
Section: Uv Visual Signals In Aggressive Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several examples from vertebrates indicate that UV reflectance influences the escalation and duration of maleemale competition in the damselfish Pomacentrus amboinensis (Siebeck, 2004), threespine stickleback, Gasterosteus aculeatus (Rick & Bakker, 2008), Augrabies flat lizard, Platysaurus broadleyi (Stapley & Whiting, 2006;, blue tit, Cyanistes caeruleus (Remy, Gregoire, Perret, & Doutrelant, 2010), and eastern bluebird, Sialia sialis (Siefferman & Hill, 2005). Yet only a handful of studies have shown that UV reflectance affects the outcome of maleemale competition in vertebrates, including the European green lizard Lacerta viridis (Bajer, Molnar, Torok, & Herczeg, 2011) and blue tit (Vedder, Schut, Magrath, & Komdeur, 2010), and few studies have been conducted in field populations.…”
mentioning
confidence: 99%
“…We conclude that, in blue tits, UV-blue crest coloration 34 affects both social and aggressive responses towards unfamiliar individuals, and thus 35 it has some properties of a badge of status. 36 potentially familiar individuals, whereas a second study (Vedder et al 2009) found 100 that UV coloration influenced pairwise contest outcomes between unfamiliar males. 101…”
mentioning
confidence: 99%